Efficacy of Liuzijue Qigong in Individuals with Chronic Obstructive Pulmonary Disease in Remission - Xiao, Chun-Mei; Zhuang, Yong-Chang (Journal of the American Geriatrics Society (JAGS), 2015)
Objectives To investigate the effectiveness of a 6‐month Liuzijue qigong (LQG) program in promoting physical and psychosocial function in individuals with chronic obstructive pulmonary disease (COPD). Design Single‐blind, randomized controlled trial. Setting Seven hospital respiratory care centers in Beijing. Participants Individuals with COPD (N = 126; mean age 71.1 ± 2.7, range 65–85). Methods Participants were randomly assigned to one of two groups: LQG (n = 63) and control (n = 63). Subjects in the LQG group received a LQG program consisting of four 45‐minute sessions each week and daily walking for 30 minutes for 6 months. Control subjects walked daily for 30 minutes. Data collection was performed at baseline, at 6 weeks, and at 6 months. Primary outcomes involved functional capacity, and secondary outcomes involved quality of life. Results The LQG group had greater improvements in the 6‐minute walk test (P = .02); specific airway conductance (P = .02); monitored functional task evaluation (P = .04); Medical Outcomes Study 36‐item Short‐Form Health Survey (SF‐36; general health (P < .001), mental health (P = .03)); Chronic Respiratory Questionnaire (dyspnea (P = .05), emotion (P = .05), and mastery (P = .04) at 6‐month follow‐up. After 6 months, the control group had significant improvement only on the SF‐36 mental health (P = .02). Conclusion LQG promoted functional capacity and quality of life in older adults with COPD at 6 months and is a good alternative home exercise program for older adults in the rehabilitation of COPD.